RIBA DALAM PERSPEKTIF AL-QURAN - Has, Muhammad Hasdin (Institut Agama Islam Negeri Kendari, 2016)
his paper aims to understand the meaning and essence of usury in the Koran, thus providing a complete understanding to distinguish transactional practices that have prevailed in the Arab community, including the sale and purchase and to understand the Qoran solutions to combat the practice of usury. Using descriptive analysis method with socio-historical approach to interpretation, verses that discuss usury, analyzing and linking (absurd) between verses on usury. The first result, that usury question is ad'afan mudh'afatan happens to contain elements of economic practices ekploitasi. secondly, usury actors experience the chaos and confusion in life and last the Qoran offers charity (including alms) as a concept ta'awwun (help) to those in need